2014
DOI: 10.1155/2014/973638
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Irrigation with Treated Wastewater on Root and Fruit Mineral Elements of Chemlali Olive Cultivar

Abstract: Twenty-year-old “Chemlali” olive trees trained to vase and rainfed were investigated in either “on” (2004) or “off” (2003) year. A randomized block design with three blocks and three treatments was used and each experimental plot consisted of nine olive trees. Three treatments were applied: (1) rainfed conditions (RF, used as control treatment); (2) irrigation with well water (WW); and (3) irrigation with treated wastewater (TWW). Irrigation with TWW led to a significant increase of root N, P, Ca, Zn, Mn, Na, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 32 publications
(55 reference statements)
1
19
0
Order By: Relevance
“…There are some studies where the saline RW has been used to irrigate olive trees in Mediterranean countries (Greece, Israel, Italy, Spain, Jordan, Egypt, and Tunisia), which reported that the tolerance to salinity depends on the olive varieties. Most of the works evaluated soil properties and leaf nutrients (Aragüés et al, 2005; Ben Rouina et al, 2011; Segal et al, 2011; Petousi et al, 2015; Bourazanis et al, 2016; Erel et al, 2019), root nutrient (Bedbabis et al, 2014), vegetative growth (Kchaou et al, 2010; Ben-Gal et al, 2017), fruit nutrient (Melgar et al, 2009; Batarseh et al, 2011; Bedbabis et al, 2014), and oil yield and quality (Melgar et al, 2009; Ayoub et al, 2016; Tietel et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are some studies where the saline RW has been used to irrigate olive trees in Mediterranean countries (Greece, Israel, Italy, Spain, Jordan, Egypt, and Tunisia), which reported that the tolerance to salinity depends on the olive varieties. Most of the works evaluated soil properties and leaf nutrients (Aragüés et al, 2005; Ben Rouina et al, 2011; Segal et al, 2011; Petousi et al, 2015; Bourazanis et al, 2016; Erel et al, 2019), root nutrient (Bedbabis et al, 2014), vegetative growth (Kchaou et al, 2010; Ben-Gal et al, 2017), fruit nutrient (Melgar et al, 2009; Batarseh et al, 2011; Bedbabis et al, 2014), and oil yield and quality (Melgar et al, 2009; Ayoub et al, 2016; Tietel et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Arbosana, despite being a cultivar widely cultivated has been under-assessed; only Kchaou et al (2010) studied it in a greenhouse pot experiment with nutrient solution. Indeed, most of works used other olive cultivated varieties, such as Barnea, Leccino (Segal et al, 2011; Ben-Gal et al, 2017; Erel et al, 2019; Tietel et al, 2019), Arbequina (Aragüés et al, 2005; Rosecrance et al, 2015; Hernández et al, 2018; Hernandez-Santana et al, 2018), Chemlali (Ben Rouina et al, 2011; Bedbabis et al, 2014; Bedbabis and Ferrara, 2018), Koroneiki (Petousi et al, 2015; Bourazanis et al, 2016), Nabali Muhassan (Ayoub et al, 2016), Frantoio (Gucci et al, 2019), and Picual (Melgar et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The total soluble solids in the fruits were determined using a digital refractometer. Fruits were sampled in triplicate of each treatment (each sample one gram) [ 14 , 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…They can also transport toxic pollutants into catchments [12] with potential transfer to the food chain. Good quality water resources are of becoming more and more scarcity of conventional water resources, due to water demand increases both for human consumption and for agricultural use, the reuse of saline, brackish, and treated waste water could be a realistic way for reducing water shortage, as it has been demonstrated in many countries in the Mediterranean basin [13]. Effluent differs from fresh water for salinity, pH and concentrations of micro-elements and nutrients.…”
Section: Introductionmentioning
confidence: 99%